New and Emerging Challenges of the ICT-Mediated Health and Well-Being Services - Lahtiranta, Janne (Turku Centre for Computer Science, 2014)
This monograph dissertation looks into the field of ICT-mediated health and well-being services. Through six chapters that extend the work done in the reviewed and published articles, the dissertation focuses on new and emerging technologies, and to impact of their use on the beneficiary; the individual who eventually derives advantage from the services. As the field is currently going through major changes particularly in the OECD countries, the focus is on shortterm developments in the field and the analysis on the long term developments is cursory by nature. The dissertation includes theoretical and empirical elements. Most of the empirical elements are linked to product development and conceptualization performed in the national MyWellbeing project that ended in 2010. In the project, the emphasis was on conceptualization of a personal aid for the beneficiary that could be used for managing information and services in the field of health and well-being services. This work continued the theme of developing individual-centric solutions for the field; a work that started in the InnoElli Senior program in 2006. The nature of this thesis is foremost a conceptual elaboration based on a literature review, illustrated in empirical work performed in different projects. As a theoretical contribution, this dissertation elaborates the role of a mediator, i.e. an intermediary, and it is used as an overarching theme. The role acts as a ‘lens’ through which a number of technology-related phenomena are looked at, pinned down and addressed to a degree. This includes introduction of solutions, ranging from anthropomorphic artefacts to decision support systems that may change the way individuals experience clinical encounters in the near-future. Due to the complex and multiform nature of the field, it is impractical and effectively impossible to cover all aspects that are related to mediation in a single work. Issues such as legislation, financing and privacy are all of equal importance. Consideration of all these issues is beyond the scope of this dissertation and their investigation is left to other work. It follows from this that the investigation on the role is not intended as inclusive one. The role of the mediator is also used to highlight some of the ethical issues related to personal health information management, and to mediating health and well-being related issues on behalf of another individual, such as an elderly relative or a fellow member of a small unit in the armed forces. The dissertation concludes in a summary about the use and functions of the mediator, describing some potential avenues for implementing such support mechanisms to the changing field of ICT-mediated health and well-being services. The conclusions also describe some of the limitations of this dissertation, including remarks on methodology and content.